2015
DOI: 10.1016/j.techfore.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic indicators for integrated assessment models of climate policy

Abstract: International audienceIntegrated assessments of how climate policy interacts with energy-economy systems can be performed by a variety of models with different functional structures. In order to provide insights into why results differ between models, this article proposes a diagnostic scheme that can be applied to a wide range of models. Diagnostics can uncover patterns of model behavior and indicate how results differ between model types. Such insights are informative since model behavior can have a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 17 publications
1
93
0
3
Order By: Relevance
“…(1) See Methods for discussion of which fuels are depicted in which model. (2) The TI-p or the Transformation Index (primary energy) classification of model behavior under carbon taxes from Kriegler et al 9 . "Low" indicates a relatively smaller transformation of primary energy supply compared to other models whereas "High" indicates a relatively larger transformation of the primary energy system compared to other models.…”
Section: Supplementary Figure 12 Comparison Of Our Baselines To Thementioning
confidence: 99%
See 2 more Smart Citations
“…(1) See Methods for discussion of which fuels are depicted in which model. (2) The TI-p or the Transformation Index (primary energy) classification of model behavior under carbon taxes from Kriegler et al 9 . "Low" indicates a relatively smaller transformation of primary energy supply compared to other models whereas "High" indicates a relatively larger transformation of the primary energy system compared to other models.…”
Section: Supplementary Figure 12 Comparison Of Our Baselines To Thementioning
confidence: 99%
“…"Low" indicates a relatively smaller transformation of primary energy supply compared to other models whereas "High" indicates a relatively larger transformation of the primary energy system compared to other models. (3) CoEI or the carbon intensity over energy intensity indicator characterizes model behavior under carbon taxes from Kriegler et al 9 . "Low" indicates models which have a stronger reduction in carbon intensity relative to energy intensity compared to other models whereas "High" indicates models which have a stronger demand response compared to growth in low carbon energy sources.…”
Section: Supplementary Figure 12 Comparison Of Our Baselines To Thementioning
confidence: 99%
See 1 more Smart Citation
“…We particularly zoom in on electricity generation, as in developing countries (and especially in Latin America), this sector is likely to grow fast over the decades to come, with a two-to three-fold expansion between today and 2050 (see for example IEA-ETP, 2012. A number of recent studies have shown that the decarbonization of non-electric energy supply, such as in the transport sector and industry, poses crucial challenges for low atmospheric CO 2 concentration stabilization, since either fewer technology options exist or low-carbon technologies abound but are more expensive than for electricity generation (see e.g., Krey et al, 2014;Kriegler et al, 2014aKriegler et al, , 2014bLuderer et al, 2012;Rösler et al, 2014;van der Zwaan et al, 2013a). A detailed inspection of these other sectors, however, is beyond the scope of the present paper.…”
Section: Introductionmentioning
confidence: 96%
“…In this paper we also inspect the reasons for differences in technology roll-out that we observe across models, some of which relate to structural differences between models, others to different parameter assumptions (see e.g. Kriegler et al, 2014aKriegler et al, , 2014b, who present results of extensive analysis in an effort to do the same through novel work on the basis of diagnostic indicators).…”
Section: Introductionmentioning
confidence: 99%